Designing a Website-Based Inventory Information System at 'NeoSkin' Cosmetics Store Using User-Centered Design - Evlyn Jane Putri; Devi Fedrianingsih; Meilani Jesica; Irfan Tigranaufal Nugraha; Danke Hidayat; Ramma Dwi Rachmat; Mahatmadi Ariq Mayangkara; Ade Riyanti; Afifah Rodhiyatun Nisa (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
Inventory system plays an important role in managing inventory in the warehouse, especially for companies engaged in product sales. in the field of product sales. NeoSkin, as one of the cosmetics stores, needs an effective and efficient system to manage inventory reports. an effective and efficient system to manage inventory reports in a structured manner. in a structured manner. This research aims to design and develop web-based Inventory Information System at NeoSkin cosmetics store, with a User Centered Design (UCD) approach that focuses on the needs of users. User Centered Design (UCD) approach that focuses on the needs and experience of users. user experience. Black Box Testing is used to ensure that the system system functions properly and according to user needs.